فاعلية برنامج تدريبي قائم على تحسين الانتباه في إكساب مهارات اللغة للتلاميذ المعاقين فكريا بالطائف - السليمانى، عبدالله على عبدالله; عيسى، ماجد محمد عثمان محمد Issa, Majed Mohammed Othman (المؤسسة العربية للتربية والعلوم والآداب, 2018)
The current research attempts to Identify the effectiveness of a training program based on improving of attention in Language acquisition skills for Intellectual disability pupils in Taif, and. the extent to which they maintain this improvement. The study used a semi empirical approach. Its sample consisted of 20 male pupils divided into two groups . Their ages range from 15 to 18 years. The first group was the experimental group (10) pupils and the second group was the controlling group (10) pupils. The experimental group has been given the training program prepared by the researcher. The Language skills scale prepared by the researcher havebeen applied before and after (pre/post test) the program. The findings indicated that there are statistically significant differences in mean ranks between the two groups in post test for experimental group in language skills. Also, the findings indicated that there are no statistically significant differences between the mean ranks of the experimental group, and between the post and followed test in Language skills. In the light of the findings of the study results , it has been provided some recommendations, and proposed future research
هدفت الدراسة الحالية إلى التعرف على فاعلية برنامج تدريبي قائم على تحسين الانتباه في إكساب مهارات اللغة للتلاميذ المعاقين فكريا بالطائف. ومدى استمرار هذا التحسين، وقد استخدمت الدراسة المنهج التجريبي ، وتكونت عينة الدراسة من (٢٠) تلميذا من الذكور المعاقين فكريا، تتراوح أعمارهم ما بين (١٥ – ١٨) سنة ، تم تقسيمهم إلى مجموعتين الأولى تجريبية قوامها (10) تلاميذ والثانية ضابطة قوامها (10) تلاميذ ، وقد تعرضت المجموعة التجريبية للتدريب على برنامج لتحسين الانتباه (إعداد الباحث) ، وطبق مقياس المهارات اللغوية (إعداد الباحث) قبل وبعد البرنامج على المجموعتين وأشارت النتائج إلى وجود فروق ذات دلالة إحصائية بين متوسطات رتب درجات أفراد المجموعة التجريبية ومتوسطات رتب درجات المجموعة الضابطة في المهارات اللغوية في القياس البعدي لصالح المجموعة التجريبية ، وعدم وجود فروق ذات دلالة إحصائية بين متوسطات رتب درجات أفراد المجموعة التجريبية في المهارات اللغوية في القياس البعدي والتتبعي. وفي ضوء ما توصلت إليه الدراسة من نتائج تم عرض عدد من التوصيات والبحوث المقترحة.
Keywords: البرامج التدريبية -- تدريس اللغة -- المهارات اللغوية -- الإعاقة الفكرية -- الطلاب المعاقين -- الطائف -- السعودية